Essays on 'the welfare state' / Richard M. Titmuss. - Titmuss, Richard Morris, 1907-1973 (Policy Press, 2018)
This reissued classic contains a selection of Richard Titmuss (1907-1973) most famous writings on social issues. It covers subjects from the position of women in society and changes in family life to the problems of an ageing population, pensions, social security and taxation policy, and the development of the national health service.